Self-Regulation And Learning Motivation of Guidance And Counseling’s Students, FKIP, UNDANA, Toward Online-Based Learning During Covid-19 Pandemic - Katharina E. P. Korohama; Andriani Paulin Nalle; Khetye Romelya Saba; Lolang M (International Journal of Social Service and Research, 2021)
This study aims to measure self-regulation and learning motivation of university students of Guidance and Counselling (BK) Department, FKIP, Undana in third, fifth and seventh semester students participating in online-based learning during the Covid-19 pandemic. The method used was a mixed method, which combines quantitative and qualitative ways. The data was collected by distributing questionnaires through online way and by conducting FGD (Focused group Discussion) using the Zoom application. The results show that there is a positive correlation between self-regulation and learning motivation. It means that the higher the students’ self-regulation, the higher the motivation to learn in attending lectures online, and vice versa. Furthermore, the students show high intrinsic learning motivation because they are supported by self-regulation and high self-efficacy and good adaptability. Therefore, it is suggested for students to maintain their self-regulating skill, increase self-efficacy and adaptability so that they can maintain learning motivation in online lectures, especially intrinsic learning motivation during Covid 19 pandemic situation